MODEL PEMBELAJARAN PEER GROUP UNTUK PENINGKATAN KEMANDIRIAN BELAJAR MAHASISWA - Anan Sutisna (Perspektif Ilmu Pendidikan, 2011)
The purpose of this research is to unveil the instructional model which can strengthen the self-learning competence of the university students. A peer group instructional model is choosen as the alternative model to develop. The research findings indicate that (1) the university students’ learning tends to be textbook centered based instruction and does not motivate the students to develop their learning strategy, (2) peer group instructional model can improve the students’ competence in self-learning, formulating the objectives, planning the strategy, utilizing learning resources, using media, comprehending the main ideas in the learning materials, exposing ideas, understanding learning networks, and measuring learning achievement.